A THERMO-ECONOMIC COMPARISON OF THE UP-THERM HEAT CONVERTER AND AN ORGANIC RANKINE CYCLE HEAT ENGINE - Kirmse,CJW; Oyewunmi,OA; Haslam,A; Markides,CN (2016)
In this paper we compare a recently proposed two-phase thermofluidicoscillator device termed ‘Up-THERM’ to a basic(sub-critical, non-regenerative) equivalent organic Rankine cycle(ORC) engine. In the Up-THERM heat converter, a constanttemperature difference imposed by an external heat source andsink leads to periodic evaporation and condensation of the workingfluid, which gives rise to sustained oscillations of pressureand volumetric displacement. These oscillations are convertedin a load arrangement into a unidirectional flow, which passesthrough a hydraulic motor that extracts useful work from the device.A pre-specified Up-THERM design is being considered in aselected application with two n-alkanes, n-hexane and n-heptane,as potential working fluids. One aim of this work is to evaluatethe potential of this proposed design. The thermodynamic comparisonshows that the ORC engine outperforms the Up-THERMheat converter in terms of power output and thermal efficiency,as expected. An economic comparison, however, reveals that thecapital costs of the Up-THERM are lower than those of the ORCengine. Nevertheless, the specific costs (per unit power) favourthe ORC engine due to its higher power output. Some aspects ofthe proposed Up-THERM design are identified for improvement